Mediating Living Heritage: A Research-through-Design Approach to Sustainable Interior Strategies for Shanxi Lacquerware - Hao, Peiru (International Journal of Humanities and Social Science, 2026)
This study investigates how interior design interventions can enhance the sustainability of living heritage through experiential and participatory spatial strategies. Using a lacquerware studio in Shanxi Province, China, as a research-through-design case, the project explores how interior space can mediate relationships between traditional craftsmanship, contemporary consumption, and cultural transmission. Grounded in the concept of living heritage and aligned with United Nations Sustainable Development Goal 12 (Responsible Consumption and Production), the research adopts a qualitative, practice-led methodology in which design functions as a mode of inquiry. Through material experimentation, spatial prototyping, and contextual analysis, the study proposes a "Scrap-to-Texture" material strategy and a topological spatial layout to foster public engagement and material reuse. Findings suggest that interior design can serve not merely as a representational medium, but as an active agent in reconfiguring heritage practices within everyday contexts, thereby contributing to sustainable cultural continuity.